Impact of the DRD2 Polymorphisms on the Effectiveness of the Training Program - Katarzyna Świtała (International Journal of Environmental Research and Public Health, 2022)
Dopamine receptor D2 gene (DRD2) polymorphisms have been associated with cognitive abilities, obesity, addictions, and physical-activity-related behaviors, which may underlie differences in the effectiveness of training programs. What is not yet clear is the impact of DRD2 polymorphisms on the effectiveness of exercise programs. Thus, the aim of this study was to investigate the association between the DRD2 polymorphic sites (rs1076560, rs12364283, rs1799732, rs1800497, and rs1800498) and the body’s response to regular physical activity. We studied genotypes and haplotypes distribution in a group of 165 females measured for body mass and body composition measurements, lipid profile, and glucose levels before and after realization of a 12-week training program. When tested individually, statistical analyses revealed one significant genotype by training interaction under the general model (for the basal metabolic rate, BMR, p = 0.033). Carriers of the rs1076560 CC genotype exhibited a decrease in BMR in response to training (p = 0.006). Haplotype analyses also showed that (i) the CACCC and CACTT haplotypes were associated with a post-training decrease in glucose level (β = −4.11, p = 0.032; β = −6.86, p = 0.020, respectively); (ii) the CGCCT with an increase in BMR (β = 0.65, p = 0.003) and fat free mass (FFM, β = 1.20, p = 0.009); (iii) the CA-CT with a decrease in low-density lipoprotein cholesterol (LDL, β = −17.26, p = 0.046). These results provide some evidence that the DRD2 polymorphisms may play a role in post-training changes in lipid and carbohydrate metabolism, and, as a consequence, in the effectiveness of training programs.